Selecting Shoes Box Suppliers using DEMATEL-ANP-WZOGP Approach: Seleksi Pemasok Kemasan Sepatu dengan Pendekatan DEMATEL-ANP-WZOGP - Gunawan, Ivan; Trihastuti, Dian; Sianto, Martinus Edy; Godelva, Ivena (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
Supplier selection is an important stage in the procurement of goods and services. The suitable suppliers will streamline the company's business processes to increase profits for the company. Product packaging is one of the vital components of the overall representation of a product. Many industries leave packaging matters to others to focus on their area of specialization. Thus, the selection of packaging suppliers has become one of the critical issues in the industrial world. This study aims to develop a packaging supplier selection model in the shoe industry. The primary packaging for shoes is a shoe box made of cardboard. In developing the packaging supplier selection model, it is necessary to determine the relevant criteria and sub-criteria to support the entire supplier selection process. The integration of the Decision-Making Laboratory and Evaluation Laboratory (DEMATEL), Analytic Network Process (ANP), and Weighted Zero-One Goal Programming (WZOGP) were used in this study to produce a suitable supplier selection model. In the initial step, five criteria and 12 sub-criteria were determined from the literature study and brainstorming with the procurement department. Furthermore, the DEMATEL method supports the development of a model of the relationship between criteria, sub-criteria, and alternatives required in the ANP procedure. Then, the ANP method synergistically assigns weights to each criterion, sub-criteria, and alternative. The weights from the results of the ANP method are used as parameters for the WZOGP optimization model. In this study, quality (28.1%) was ranked as the highest criterion, and shoe box prints that matched the specifications (12.3%) became the sub-criteria with the highest ranking. The selection of the best suppliers using the ANP method sequentially is supplier B (62.22%), supplier A (20.41%), and supplier C (17.38%). The results of the WZOGP optimization model confirm the results of the ANP by setting supplier B as the leading supplier